Transfer Queen - Strouse, A.W (punctum books, 2018)
Cruising the New York City subway, the Transfer Queen is on the prowl! These voyeuristic figure drawings-both poetic and visual-sketch the men of Gotham's transportation system. A.W. Strouse and Patty Barth spy on strangers with a special kind of anonymous intimacy. Transfer Queen is ideal reading material for kinky commuters. But remember: "A crowded subway car is no excuse for unlawful sexual conduct!"